PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L.) PADA BERBAGAI DOSIS PUPUK KANDANG - Burhanudin Latarang; Abdul Syakur (Universitas Tadulako, 2006)
This experiment, done at Guntarano Village, North Palu from August to December 2004, was intended to study the growth and yield responses of shallot crop to the application of animal manure as an organic fertilizer. The experiment was carried out using a completely randomised design with six levels of manure application, each of which was replicated three times. These treatments were without manure and with manure applied at 2 t/ha, 10 t/ha, 15 t/ha, 20 t/ha and 25 t/ha. Results showed that the highest shallot growth and yields were obtained when the manure was applied at 25 t/ha.